2019
DOI: 10.1063/1.5086800
|View full text |Cite
|
Sign up to set email alerts
|

Modification of ITO anodes with self-assembled monolayers for enhancing hole injection in OLEDs

Abstract: Increasing carrier injection efficiency is an important way to improve the performance of organic light-emitting diodes (OLEDs). In this work, self-assembled monolayers (SAMs) were formed on indium tin oxide (ITO) anodes with different aromatic carboxylic acids. The relationship between the molecular structure and its effect on modification was investigated. The presence of monolayers was verified by X-ray photoelectron spectroscopy. Water contact angle tests show that the surface energy of ITO has decreased a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…In addition, for other conjugated SAM systems, An et al suggested that as the electronic cloud distribution of the HOMO of the SAM becomes more aggregated and continuous, the rate of hole transfer enhances. 53 Whether this conclusion also applies to the different SAMs studied here remains to be determined. It can be suggested that the enhanced hole transfer rate and FF for Me-4PACz could be related to the $0.1 eV increase in the WF observed for Me-4PACz (Figure 2A), leading to an increase in the barrier height for electron transfer to the ITO (F B,e in Figure 1A).…”
Section: Ll Open Accessmentioning
confidence: 84%
“…In addition, for other conjugated SAM systems, An et al suggested that as the electronic cloud distribution of the HOMO of the SAM becomes more aggregated and continuous, the rate of hole transfer enhances. 53 Whether this conclusion also applies to the different SAMs studied here remains to be determined. It can be suggested that the enhanced hole transfer rate and FF for Me-4PACz could be related to the $0.1 eV increase in the WF observed for Me-4PACz (Figure 2A), leading to an increase in the barrier height for electron transfer to the ITO (F B,e in Figure 1A).…”
Section: Ll Open Accessmentioning
confidence: 84%
“… 34 It is well known that SAMs form a dipole layer on the metal substrate, which can be used, and engineered, for work function modification of the metal substrate, and therefore for optimizing charge transfer between the metal electrode and organic semiconductor formed on these SAMs via tuning the relative position of the metal Fermi level and the highest occupied molecular orbital (HOMO) or lowest unoccupied molecular orbital (LUMO) levels of the organic semiconductor. 35 38 Such dipole layer based on SAMs consists of two components related to the molecular dipole and the interfacial dipole created by the chemical bonding of the anchoring group to the metal substrate. 35 For (Gly) n Cys-based SAMs, the change of the metal substrate induces modification of both components, and therefore, a shift in BE is expected.…”
Section: Results and Discussionmentioning
confidence: 99%
“…To reflect all the light towards the anode direction, a thick metal cathode such as aluminum (Al) was used. For the anode, high-transmittance indium tin oxide (ITO) was typically used to emit as much light as possible [30,31]. There was a strong and weak reflection in the cathode and the anode, respectively.…”
Section: Optical Theorymentioning
confidence: 99%